Estimasi Populasi Orang Utan dan Model Perlindungannya di Kompleks Hutan Muara Lesan Berau, Kalimantan Timur - M. Bismark (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2005)
Orang utan (Pongo pygmaeus) is a protected animal with restricted distribution was only in Sumatera and Kalimantan. With its restricted habitat and population in the conservation area, the occurrence of forest degradation would have significant impact to the habitat and population of this species, therefore forest area outside conservation area became important for conservation of orang utan. In this matter, production forest had been known as essential ecosystem for orang utan conservation objective. Population of orang utan was studied in Muara Lesan, former Concession Area of PT Alas Helau, Berau, East Kalimantan that covered area of 12,228 ha, with method of nest counting. Nest counting was carried out in transect lines 500-1000 m length. Total length of lines within transect was 28 km, or equal with 5.7 percent of study area. Population density of orang utan in Muara Lesan was between 1.92-7.13 individuals/km² (average of 3.69 individuals) with total population of 365-450 individuals. Estimation of population by nest counting method was influenced by age of nest (new to 285 days old), potency of food trees, movement behavior, including migration and condition of habitat. Based on its total population, orang utan in this area was categorized as critical. Protection of orang utan habitat and population in Forest Concession Areas of Kalimantan, in its management should determine sufficient conservation area, or should propose essential ecosystem for habitat and population of orang utan in former area of forest concession that was not managed as conservation area. AbstrakOrang utan (Pongo pygmaeus) adalah satwa langka yang dilindungi dengan penyebaran yang sangat terbatas di Sumatera dan Kalimantan. Dengan terbatasnya habitat dan populasi orang utan yang termasuk dalam kawasan konservasi, terjadinya degradasi hutan yang berdampak penting bagi habitat dan populasi, maka kawasan hutan di luar kawasan konservasi menjadi penting untuk pelestarian orang utan. Dalam hal ini hutan produksi telah diketahui sebagai ekosistem esensial untuk tujuan pelestarian. Populasi orang utan yang diteliti di kawasan Muara Lesan eks HPH PT Alas Helau seluas 12.228 ha dilakukan dengan metode penghitungan sarang. Penghitungan sarang dilakukan dalam jalur yang dibuat pada transek 500-1000 m. Dengan panjang total jalur 28 km, areal survei setara dengan 5,7% luas kawasan. Kerapatan populasi orang utan di Muara Lesan berkisar antara 1,92-7,13 individu/km² (rata-rata 3,69 individu) dengan jumlah total populasi 365-450 individu. Estimasi populasi dengan metode penghitungan sarang ini dipengaruhi oleh umur sarang yang mencapai 285 hari, potensi pohon pakan, perilaku pergerakan, termasuk migrasi serta kondisi habitat. Berdasarkan jumlah total populasi, orang utan di kawasan ini tergolong dalam populasi kritis. Perlindungan habitat dan populasi orang utan di kawasan HPH di Kalimantan, dalam pengelolaannya harus menetapkan wilayah konservasi yang cukup atau mengusulkan ekosistem esensial bagi habitat dan populasi orang utan di areal eks HPH yang tidak dikelola menjadi kawasan konservasi.